A study on the causes and the ir treatment results of the dystocia in cows observed between 1985- 1992 years in elazığ region - Cahit Kalkan; Hüseyin Deveci; A. Mükremin Apaydın; Halis Öcal; Hüseyin Timurkan; Hayrettin Çetin; Erdal Kaygusuzoğlu (Eurasian Journal of Veterinary Sciences)
In this study, the causes, treatment methods and results obtained after treatment of the dystocia observed between 1985- 1992 years in Elazığ region were investigated. In the study, 195 cows and heifers aged 2-10 years were use d as material. These animals were treated aither in the Clinic of Obstetrics and Gynecology Faculty of Veterinary Medicine, Fırat University or in the places where the animals are held. It has been understood that these dystocia resulted from fet al and matem al causes in the rations of 72.68 % and 27.32 %, respectively. The fetal causes were anormal postures with 30.63 % and relative or absolut growth with 18.82 %. The main one of the maternal causes was uterine inertia w ith 10.33 %. The calvas included 72.4 % ma/e and 27.6 % female. These fetuses were found to enter into the pelvic canal 74.17% anteriorly, 21.85 % posteriorly and 3.9 % transversally The mortality ratio of the calvas due to the dystocia was 27.6 %. 94.87% of the fetuses treated within the first 10 hours and 48. 72% of the ones treated from 10 hours were delivered alive.